LEADERSHIP PRACTICES AT PUBLIC HIGH SCHOOLS IN GABORONE, BOTSWANA - More-Keddy, Gotlhe K; Mpuangnan, Kofi Nkonkonya; Dick-Sagoe, Christopher; Roboji, Zukiswa (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
Effective leadership in education is crucial for fostering a positive and supportive learning environment. The state of leadership in schools, particularly in developing countries, is often perceived as inadequate. This study aims to investigate leadership styles in Gaborone's public high schools in Botswana. It focused on gender leadership style choices in management, the prevalent leadership styles among Gaborone's public secondary school leaders, and the most effective leadership styles for fostering success in educational settings within the city. In line with these focal points, a descriptive survey design was employed, collecting quantitative data from fifty respondents comprising school heads, department heads, and teachers. Participants were selected using quota sampling techniques and responded to a questionnaire. The analysis utilized descriptive statistics such as frequencies, percentages, bar charts, and histograms. The findings indicated that female management in Gaborone's secondary schools predominantly favoured the Authoritative Leadership Style, followed by Transformational and Charismatic Leadership. Meanwhile, male leaders exhibited a preference for Transformational, Charismatic, and Democratic Leadership styles. Recommendations include the development of comprehensive leadership training programs tailored specifically for school management. These programs should emphasize a diverse leadership style relevant to educational contexts, fostering a more adaptable and effective leadership approach within Gaborone's school system.